2022
DOI: 10.3390/jcm11041021
|View full text |Cite
|
Sign up to set email alerts
|

Elexacaftor/Tezacaftor/Ivacaftor in Patients with Cystic Fibrosis Homozygous for the F508del Mutation and Advanced Lung Disease: A 48-Week Observational Study

Abstract: Background: Elexacaftor/tezacaftor/ivacaftor (ETI) is the newest cystic fibrosis transmembrane conductance regulator (CFTR) modulator drug approved for the treatment of patients with cystic fibrosis (pwCF) aged ≥6 years with at least one copy of the F508del mutation (F) in the CFTR gene or another mutation that is responsive to treatment with ETI. This study determined the effectiveness and safety of ETI in a cohort of severely affected pwCF with an F/F genotype. Methods: Retrospective observational study in F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
29
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 34 publications
4
29
2
1
Order By: Relevance
“…It is true that with the advent of ETI [ 7 , 8 ], patients’ lives have improved substantially, reducing cough, expectoration, and exacerbations and, improving digestive symptomatology and nutritional status, increasing lung function and quality of life. Thus, the onset of ITD provides an opportunity to consider reductions in the overall treatment burden [ 37 ] and assess whether other chronic medications can be safely discontinued without loss of clinical benefit.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is true that with the advent of ETI [ 7 , 8 ], patients’ lives have improved substantially, reducing cough, expectoration, and exacerbations and, improving digestive symptomatology and nutritional status, increasing lung function and quality of life. Thus, the onset of ITD provides an opportunity to consider reductions in the overall treatment burden [ 37 ] and assess whether other chronic medications can be safely discontinued without loss of clinical benefit.…”
Section: Discussionmentioning
confidence: 99%
“…Until a few years ago, the existing therapies were only aimed at alleviating the symptoms caused by the disease: physical exercise, physiotherapy, bronchodilators, hypertonic or mucolytic substances to improve mucociliary clearance, immunomodulators, and antibiotics to control inflammation and bronchial infection, dietary recommendations, pancreatic enzymes, and vitamin supplements to maintain a good nutritional status [ 3 ]. In recent years, CFTR (transmembrane conductance regulator protein) modulation therapy has been developed, including correctors such as Lumacaftor, Tezacaftor, and Elexacaftor and enhancers such as Ivacaftor, which respectively repair and activate chloride channel function, improving the characteristics of secretions from all organs [ 4 , 5 , 6 , 7 , 8 ]. These treatments are currently indicated in patients heterozygous or homozygous for the F508del mutation and are leading to a major change in the lives of these patients with minimization of most symptoms, which may result in a reduction or abandonment of symptomatic treatment [ 4 , 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Across all three studies, improvement in percentage of predicted FEV 1 (ppFEV 1 ) indicated better lung function, lower sweat chloride concentrations and a higher Cystic Fibrosis Questionnaire-Revised respiratory domain (CFQ-R RD) score indicating less respiratory symptoms and a better overall quality of life ( Zaher et al, 2021 ). Furthermore, an observational study in PwCF homozygous for the F508del mutation ranging from 20.8 to 48.3 years old (median age = 31.1 years) taking TRIKAFTA ® over the course of 48 weeks was done ( Carnovale et al, 2022 ). Although inflammation was not evaluated, an improvement in FEV 1 , body mass index and sweat chloride was observed.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is important to note that due to COVID-19, CF clinics have seen less bacterial exacerbations since patients were isolating and wearing masks. This is relevant given it is a retrospective study (i.e., without adequate control group comparisons) ( Carnovale et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%